Hepatitis E virus seroprevalence, seroincidence and seroreversion in the German adult population. Issue 6 (1st March 2018) - Faber, M.; Willrich, N.; Schemmerer, M.; Rauh, C.; Kuhnert, R.; Stark, K.; Wenzel, J. J.
Summary: A steep rise in Hepatitis E diagnoses is currently being observed in Germany and other European countries. The objective of this study was (i) to assess whether this trend mirrors an increase in infection pressure or is caused by increased attention and testing and (ii) estimate individual and population‐based Hepatitis E Virus (HEV) seroconversion and seroreversion rates for Germany. We measured anti‐HEV IgG prevalence in 10 407 adults participating in two linked, population‐representative serosurveys (total n = 12 971) conducted in 1998 and 2010. In this period, we found a moderate but statistically significant decline of overall anti‐HEV IgG prevalence from 18.6% to 15.3%. At both time points, seroprevalence increased with age and peaked in persons born between 1935 and 1959 suggesting a past period of increased infection pressure. Paired samples of individuals participating in 1998 and 2010 (n = 2564) revealed respective seroconversion and seroreversion rates of 6.2% and 22.6% among seronegative and seropositive individuals during 12 years, or 5.2 and 2.9 per 1000 inhabitants per year. This corresponds to a total of 417 242 [95%CI: 344 363‐495 971] new seroconversions per year in the German population. While anti‐HEV seroprevalence has decreased in the last decade, infection pressure and seroincidence remains high in Germany. Continuously rising numbers of Hepatitis E diagnoses in Europe are likely due to an increased awareness of clinicians and indicate that still there is a gap between incident and diagnosed cases. Studies on the true burden of the disease, specific risk factors and sources of autochthonous infections as well as targeted prevention measures are urgently needed.